VIRTUAL TOURISM DALAM LITERATURE REVIEW - Rafidola Mareta Riesa; Alfatah Haries (Akademi Pariwisata Bunda Padang, Sumatera Barat, Indonesia, 2020)
The spreads of coronavirus bring major impact on travel and tourism sectors. The lockdown policy and travel restriction has ban people from traveling. The areas quarantine in West Sumatera has decrease numbers of visitors visiting tourism attractions. More people staying at home because of the coronavirus pandemic resulting the needs of alternative way of traveling becomes necessary. This research will explore the alternative ways of travelling during the pancemic. The research finding is that virtual tourism can be one of the alternative ways of traveling for tourists.